The speed of change : motor vehicles and people in Africa, 1890-2000 - Gewald, Jan-Bart; Luning, Sabine; van Walraven, Klaas (Leiden: Brill; Boston, 2009)
"Edited by Jan-Bart Gewald, Sabine Luning and Klaas van Walraven"